Enhancing Enzymatic Digestibility and Lignin Production of Oil Palm Empty Fruit Bunch (OPEFB) by Green Deep Eutectic Solvent - Urania Noor Lintang Pertiwi; Tabina Raissa Apol; Ika Putri Nikmatur Rohmah; Maktum Muharja; Tri Widjaja; Lieke Riadi; Arief Widjaja; Candra Wijaya (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Oil palm empty fruit bunch (OPEFB) is an abundant lignocellulosic residue whose high lignin content restricts its bioconversion into sugars and value-added products. Deep eutectic solvents (DESs), particularly choline chloride–lactic acid, offer a green and tunable platform for selective delignification and biomass fractionation. This study investigates the effects of ChCl:LA (1:2) DES pretreatment under varying temperatures (100–140 °C) and reaction times (3-6 h) on the chemical composition, structural modification, delignification kinetics, and enzymatic digestibility of OPEFB. A modified combined delignification factor (CDF) was developed to unify temperature, time, and DES acidity into a single severity descriptor. Delignification followed a biphasic pattern successfully captured by the CDF-based kinetic model (R² = 0.9961), with activation energy of 63.5 kJ.mol⁻¹. Increasing pretreatment severity enhanced hemicellulose and lignin removal (up to 95.5% and 84.4%), while cellulose remained largely preserved. SEM, XRD, and FTIR analyses confirmed progressive disruption of the lignin–carbohydrate matrix, increased cellulose exposure, and removal of amorphous domains. As a result, enzymatic hydrolysis yield improved by more than twofold relative to untreated biomass, reaching 75.5% at 140 °C for 6 h. Mass-balance evaluation demonstrated that from 100 g OPEFB, DES pretreatment yielded 21.6 g glucose and 24.7 g recoverable lignin under optimal conditions. Compared to other pretreatment strategies, the ChCl:LA DES system achieved a balanced co-production of sugars and lignin in significantly shorter processing time. Overall, this work provides mechanistic, kinetic, and mass-balance insights into DES-assisted fractionation of OPEFB and highlights its potential in integrated multiproduct biorefineries. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).